Pengaruh Media Video Animasi 2D Terhadap Aktivitas Belajar Siswa pada Mata Pelajaran IPS Kelas VIII E di SMPN 01 Sumberbaru - Zamroni Zamroni; M. Iqbal Ibrahim Hamdani; Agi Ma’ruf Wijaya (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The purpose of this study was to determine how the use of 2D animated videos impacts student learning activities in Social Studies (IPS) subjects in class VIII E at SMPN 01 Sumberbaru. The background of this study is based on the fact that conventional learning processes, which are usually monotonous and uninteresting, have low student engagement and participation. This study uses a quantitative approach using a quasi-experimental design. A non-comparable control group design was used. Questionnaires, documentation, and observation were used to collect data. The results of the study indicate that student learning activities with 2D animated video media are different from conventional learning methods. During the learning process, 2D animated video media can increase student interest, engagement, and interaction.